Conservation biology of three threatened Limonium species endemic to Zakynthos Island (Ionian Islands, Greece) - Anna-Thalassini Valli; Charikleia Papaioannou; Eleni Liveri; Vasileios Papasotiropoulos; Panayiotis Trigas (Oryx)
Knowledge of the life history traits, reproductive biology and demography of rare species is fundamental for their conservation, yet plant population monitoring is uncommon. The restricted ranges of the Limonium species endemic to the Mediterranean area, combined with the vulnerability of their specialized littoral habitats, indicate the need for appropriate conservation measures. We evaluate the conservation status and estimate the future extinction risk of three Limonium species endemic to Zakynthos Island in the Ionian Islands, Greece (Limonium korakonisicum, Limonium phitosianum and Limonium zacynthium) using 5 years of monitoring data. We compile information on their geographical distribution, population dynamics, reproductive biology and genetic diversity. Population sizes and survival rates of seedlings exhibited marked annual fluctuations, although fecundity and relative reproductive success remained high throughout the monitoring period. We observed a dominance of mature individuals in all three species, indicating their increased tolerance to salinity. Three subpopulations each of L. phitosianum and L. zacynthium were genotyped using five microsatellite loci. The observed number of alleles and the low gene flow value potentially indicate reduced genetic diversity, inbreeding, and limited gene flow within and among subpopulations of both species. Based on the IUCN categories and criteria, we assess L. korakonisicum as Critically Endangered, L. phitosianum as Near Threatened and L. zacynthium as Endangered. Population viability analyses predict that, among the three species, L. zacynthium will face the highest risk of extinction within the next 50 years. Knowledge of the biology of these species provides data essential for identifying critical factors for their survival and for proposing targeted conservation measures.